2018
DOI: 10.1039/c8tc03714k
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating a microcellular structure into PVDF/graphene–nanoplatelet composites to tune their electrical conductivity and electromagnetic interference shielding properties

Abstract: The electrical conductivity and the EMI shielding properties could be effectively tuned by the foaming degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(87 citation statements)
references
References 76 publications
3
82
0
Order By: Relevance
“…This depends on conductivity of shielding material, which is correlated with the interaction between mobile charge carriers of the material and the electromagnetic eld. 38,58,59 For the absorption, it always originates from the conduction loss (i.e., the ohmic loss) and the polarization loss. 60,61 The conduction loss is associated with attenuation of energy through the current ow via the conduction, hopping, and tunneling mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…This depends on conductivity of shielding material, which is correlated with the interaction between mobile charge carriers of the material and the electromagnetic eld. 38,58,59 For the absorption, it always originates from the conduction loss (i.e., the ohmic loss) and the polarization loss. 60,61 The conduction loss is associated with attenuation of energy through the current ow via the conduction, hopping, and tunneling mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] In addition, some researchers have found that forming a segregated structure in a composite material can make more conductive fillers contact with the matrix and produce multiple interfaces and microwaves scattered or reflected by multiple interfaces can be well absorbed by the polymer/conductive filler. [ 28–30 ] Therefore, by constructing multiple interfaces in the CPC, multiple scattering/reflection of electromagnetic waves can be enhanced, thereby improving the electromagnetic shielding performance of materials. [ 31–33 ] Li et al used cotton fiber (CTF) as the carrier to construct a lot of multiple interfaces in polydimethylsiloxane (PDMS)/MWCNT nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, researchers have focused great attention on improving the absorption properties and broadening their absorption bandwidth. Carbon based materials (carbon nanotubes (CNTs), carbon nanocoils and graphene), [4][5][6][7][8] and transition metal related materials such as metal particles (Fe, Co, Ni and their alloys), [9][10][11][12][13] oxides and hydroxides (CoO, Co 3 O 4 , NiO, MnO 2 , Fe 2 O 3 , Fe 3 O 4 , Ni(OH) 2 , MnOOH, et al), [14][15][16][17][18][19] suldes (CuS, CoS) and phosphides (FeP, Co 2 P) [20][21][22] have demonstrated excellent microwave absorption properties at certain frequency band with an optimum thickness. However, due to its electromagnetic loss mechanism, a single absorbent can hardly achieve a better performance in a wider frequency range and usually can only be used in some certain frequency.…”
Section: Introductionmentioning
confidence: 99%
“…43 Inspired by these pioneer works, combining nickel oxides or hydroxides with proper BPC materials will possess better dielectric and electrical properties and thus may be considered for electromagnetic absorbing application. In this work, using pine nut shells as the precursor, we developed a facile approach to design Ni(OH) 2 /BPC and NiO/BPC composites for EAM applications, which exhibits excellent absorption performances in the frequency range of X and Ku band (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Based on the thorough characterizations, the possible absorption mechanisms are discussed as well.…”
Section: Introductionmentioning
confidence: 99%